Die Wurzeln der Kontaktlinguistik Zur Entstehung des Sprachkontaktparadigmas in der Sprachwissenschaft unter besonderer Berücksichtigung der Rolle der Romanistik - Pagel, Steve (Heidelberg University Publishing (heiUP), 2023)
Thinking about language contact and language mixture has been part of the European-Western preoccupation with language from the very beginning. Starting with Plato in the fourth century B.C., it is for a long time an unexcited reflection, until the perspective changes radically in the 19th century: the normality is suddenly gone, contact and mixture become first a research taboo and only a little later a serious research focus, from which a separate discipline, contact linguistics, emerges. This book tells for the first time the history of the study of language contact up to the threshold of the 20th century and shows how critical-historiographical studies can help to classify and advance current debates (e.g. in creole studies).